The effects of cognitive general imagery use on tactical decision-making in curling - Westlund Stewart, N. (2016)
The general purpose of this dissertation was to determine the effects of cognitive general (CG; images of game plans and strategies) imagery use on tactical decision-making in curling. This dissertation is divided into four studies. Study 1 outlines the two-stage development of the Curling Strategy Assessment Tool (CSAT-2), a computerized measure of curlers` tactical decision-making (i.e., response accuracy and response speed). During Phase 1, 123 curlers evaluated 75 curling scenarios via an online survey. Twenty-one scenarios showed acceptable interrater agreement for a correct shot option. Pilot testing of the original version of the CSAT indicated that modifications were needed to incorporate strategy style. Thus, Phase 2 was conducted to have 93 updated scenarios assessed by three expert raters (i.e., national-level curling coaches). This process resulted in 104 scenarios that could be used to assess tactical decision-making in curlers undergoing CG imagery interventions using the CSAT-2.